Investigation of the Dynamic Characteristics of PM2.5 Dispersion During the Acceleration of Motor Vehicles in Urban Streets Based on Computational Fluid Dynamics and Dynamic Mode Decomposition - Jiawei Ding; Dan Mei; Bowen Liu; Mingwei Gao; Jiale Cui (Atmosphere)
Vehicle acceleration typically occurs at traffic lights, intersections, or congested sections within urban streets, where high densities of pedestrians and vehicles pose a direct threat to respiratory health due to PM2.5 dispersion. Computational Fluid Dynamics (CFD) simulations, combined with the Dynamic Mode Decomposition (DMD) method, are used to analyze the dynamic characteristics of PM2.5 dispersion during vehicle acceleration. The DMD method can effectively analyze the dynamic change in pollutant concentration in an unsteady flow field and clarify the influence mechanism of vehicle acceleration on pollutant dispersion. The results indicate that PM2.5 dispersion during the initial stage of acceleration is primarily influenced by low-frequency and large-scale flows, such as exhaust emissions, natural wind, and trailing vortices. In the middle stage, PM2.5 dispersion tends to stabilize, while in the final stage, high-frequency modes dominate, and intense flow field fluctuations significantly enhance PM2.5 dispersion. Furthermore, the analysis reveals the critical role of upward and downward airflow phenomena around the vehicle in driving PM2.5 dispersion. This study offers a new perspective on the dispersion characteristics of PM2.5 under unsteady flow conditions in urban streets and provides a scientific basis for developing speed management strategies to mitigate the impact of pollutant dispersion.